Corporate memory in the lean context. Preventing short- and long-term information loss - Sobral, Nuno (2019)
A large part of the information necessary for an organization to function is stored exclusively in people's memories. This applies to two different kinds of information - short-term information related to daily operations in the shop floor as well as long-term accumulated knowledge and expertise. In the present article we propose several solutions for preventing short- and long-term information loss in an industrial setting. We analyze information loss and its consequences at an automotive component factory in the North of Portugal. For the short-term information loss, we propose lean tools such as gravity flow racks, kanban and andon screens. For long-term information loss, we propose the implementation of mentorship programs, the creation of a knowledge repository based on wiki technology and the use of explanatory labels